Lethal cases of tuberculosis in children in Siberian and Far Eastern Federal Districts in 2018 - I. V. Pavlenok; O. V. Revyakina; D. V. Stepanov; V. A. Krasnov (Туберкулез и болезни лёгких, 2020)
The objective of the study: to analyze lethal cases of tuberculosis in children and adolescents in Siberian and Far Eastern Federal Districts, to determine the causes that contributed to lethal outcomes.Subjects and methods. Reports on 9 lethal outcomes of tuberculosis in children (n = 8) and adolescents (n = 1) in 2018 were retrospectively analyzed in 8 regions of Siberian and Far Eastern Federal Districts.Results. All the deceased lived in socially disadvantaged families. It was found out that parents failed to fulfill their obligations in providing care for the child. All children, except one, were vaccinated with BCG. No one had been diagnosed with HIV infection. Children under 7 years old prevailed. In 63% of cases, exposure to tuberculosis was detected. Immunodiagnosis of tuberculosis was not carried out or was irregular in the majority of cases (75% of lethal cases). All children died within 1 year of follow-up by a TB unit. Tuberculosis with lesions of the central nervous system was registered in 87.5% of lethal cases.Conclusion. The main causes contributing to the death of children due to tuberculosis were the socially disadvantaged families and the lack of attention from social service specialists, defects in the work of physicians from primary health services on the early detection of tuberculosis among children, and defects in the work of phthisiologists in the nidi of tuberculosis infections.